Why some Corporations Pay More Tax than Necessary - Karl Ove Aarbu; Jeffrey K. MacKie-Mason (Statistics Norway, Research Department, 1998)
It has been noticed in several countries that many corporations do not claim all of their allowable tax depreciation deductions, despite incurring a higher tax cost. There are several possible explanations. First, the uniform reporting accounting system (typical of many European countries) can under certain circumstances constrain dividends. The dividend constraint can, however, be loosened by forgoing some tax depreciation. We find no support for this hypothesis. Second, we find strong evidence that corporations with bad economic performance tend to underutilize their deductions, suggesting that corporations use costly "window-dressing" on their accounting measures. Third, we find support for the hypothesis that tax compliance costs discourage the utilization of accelerated depreciation, especially by small firms. Fourth, we find weak support for the hypothesis that there is substitution between tax depreciation and private debt due to competition between the benefits of private bank monitoring and the tax savings from using tax debt, as suggested in earlier literature. Our empirical analysis is possible due to unusual access to extremely detailed individual firm tax returns forms in Norway, combined with the 1992 Norwegian tax reform that provided a natural experiment for testing some of the hypotheses. We use the time-series and cross-sectional variation across Norwegian corporations in 1988, 1991, 1992 and 1993.
Keywords: D21; H25; 330; Corporate taxes; Depreciation; Reporting conventions